Proposed instructional materials in communication arts (English) for grade I - Reyes, Carmelita C. 1944- (1977)
This paper contained instructional materials for Communication Arts (English) in Grade I. It has been prepared in consonance with Bilingual Education Policy declared by the National Board on Education and in answer to the need for changes in the curricular offerings of the University of the Philippines Integrated School, particularly the kindergarten to Grade II department. There are eight lessons in this volume and each one is aimed at exposing the beginners in English to communication situations while developing their understanding of some concepts in science, health, music and art.